Saudi Novel: Commencements, Efforts, and Headway (3) - Yahya Dahami (Hasanuddin University, 2023)
The Saudi novel has experienced profound thematic and artistic development changes. Going through the Saudi novel's several stages of development may assist readers in understanding the types of aesthetic advancements made at each step. By tracing the origins, evolution, and importance of Saudi fiction, a significant literary genre, the study aims to shed light on its growth and significance. In this literary work, the researcher uses an analytical-critical approach in keeping with the nature of the literary analysis. The paper gets started with a terse outline of the conception of the novel before moving on to talk over the following topics: the literary status of Makkah Al Mukarramah and an outline of the Arabic and Saudi novel. The paper then goes on to analytically shed light on Hamid Damanhori's novel, The Price of Sacrifice. The paper finishes with recommendable discussions and a conclusion. شَهِدَتْ اَلرِّوَايَةُ اَلسُّعُودِيَّةُ تَغَيُّرَاتٍ عَمِيقَةً فِي اَلتَّطَوُّرِ اَلْمَوْضُوعِيِّ وَالْفَنِّي، قَدْ يُسَاعِدُ اَلْمُرُورُ بِمَرَاحِلِ تَطَوُّرِ اَلرِّوَايَةِ اَلسُّعُودِيَّةِ اَلْعَدِيدَةِ اَلْقُرَّاءَ فِي فَهْمِ أَنْوَاعِ اَلتَّطَوُّرَاتِ اَلْجَمَالِيَّةِ اَلَّتِي تَتِمُّ فِي كُلِّ مَرْحَلَةٍ، مِنْ خِلَالِ تَتَبُّعِ أُصُولٍ وَتَطَوُّرِ وَأَهَمِّيَّةِ اَلرِّوَايَةِ اَلسُّعُودِيَّةِ، كَوْنُهَا نَوْع أَدَبِيٍّ مُهِمٍّ، تَهْدِفَ اَلدِّرَاسَةُ إِلَى تَسْلِيطِ اَلضَّوْءِ عَلَى نُمُوّهَا وَأَهَمِّيَّتِهَا وَتَطَوُّرِهَا، يَسْتَخْدِمَ اَلْبَاحِثُ فِي هَذَا اَلْعَمَلِ اَلْأَدَبِيِّ مَنْهَجًا تَحْلِيلِيًّا نَقْدِيًّا يَتَمَاشَى مَعَ طَبِيعَةِ اَلتَّحْلِيلِ اَلْأَدَبِيِّ. تَبْدَأَ الدراسة بِمُوجز مُقْتَضَبٍ لِمَفْهُومِ اَلرِّوَايَةِ قَبْلَ اَلِانْتِقَالِ إِلَى اَلْحَدِيثِ عَنْ اَلْمَوْضُوعَاتِ اَلتَّالِيَةِ: اَلْوَضْعُ اَلْأَدَبِيُّ لِمَكَّة اَلْمُكَرَّمَةِ وَالْخُطُوطِ اَلْعَرِيضَةِ لِلرِّوَايَةِ اَلْعَرَبِيَّةِ وَالسُّعُودِيَّةِ. ثُمَّ يَنْتَقِلُ اَلْبَاحِثُ فِي هَذِهِ اَلدِّرَاسَةِ إِلَى إِلْقَاءِ اَلضَّوْءِ اَلتَّحْلِيلِيِّ عَلَى رِوَايَةِ حَمِيدِ دَمَنْهُورِي